Proposals for improvements in the biosafety of laboratories in health courses at the Federal University (Research, Society and Development, 2023)
Biosafety comprises a set of actions aimed at preventing, controlling, mitigating or eliminating risks inherent in activities that may interfere with or compromise the quality of life, human health and the environment. Given the above, the study sought to review biosafety and elaborate proposals that would contribute to the standardization of laboratories in health courses at a university in Tocantins. The study proposed a qualitative, descriptive research, through a case study. Due to this characteristic, it consisted of the survey and analysis of data and documents on the current situation of biosafety in laboratories. The methodology also involved a referential bibliographical research, in order to provide a theoretical basis for the study, as well as find subsidies to contribute to the improvement of biosafety management. The University has adopted several measures with the aim of adapting to biosafety standards, however the present study shows that the institution needs greater adequacy. It was possible to infer that teaching and research laboratories in the health area at a university in Tocantins need improvements in terms of biosafety. Such changes must be adopted not only in terms of physical structure, but also with regard to education and information directed to users. It was possible to perceive the need for institutional and academic awareness, as well as new studies with this approach in order to foster improvements in laboratory environments.